Women Empowerment and their Role in Economic Sustainability: A Critical Review of Prosperous Businesswomen of Islamic History - Dr. Muhammad Talha Hussain (Al Manhal Research Journal, 2024)
This article explores the historical contributions of successful female businesswomen in Islamic societies, shedding light on their pivotal roles in fostering economic empowerment, upholding ethical principles, and promoting overall economic prosperity. The study delves into the lives and achievements of these women, examining the unique challenges they faced within the context of Islamic history. By analysing their strategies for success, ethical considerations, and the impact of their economic endeavours, this research seeks to provide insights into the intersection of gender, commerce, and ethics in Islamic societies. Through a nuanced exploration of these historical narratives, the abstract aims to contribute to a broader understanding of the diverse role’s women played in shaping economic landscapes and ethical standards within the Islamic historical context.